Identifikasi Tumbuhan Lumut (Bryophyta) di Sekitar Air Terjun Sigerincing Dusun Tuo, Kecamatan Lembah Masurai, Kabupaten Merangin - Ardila Putri Wiadril; Rivo Yulse Viza; Rozana Zuhri (BIOCOLONY, 2018)
The background of this research is that Bryophytes are known as pioneer plants and play an important role in biodiversity. Air Terjun Sigerincing was a native forest that has changed its function to become a tourist attraction, resulting in the presence of Bryophytes that potentially damaged and disturbed by their habitat and also the lack of information regarding the identification of Bryophytes, especially in the Air Terjun Sigerincing area. The purpose of this study was to determine the type of Bryophytes in the Air Terjun Sigerincing area. This research was conducted on May 2018 with the roaming method is exploring and observing every corner of the research location. Identification of Bryophytes in the Laboratory of Biology STKIP YPM Bangko was carried on May 7, 2018. Each type of Bryophytes that was sampled and then made into a herbarium collection by inserting it into an envelope for identification purposes. During the observation and data collection the type of Bryophytes found in the field data was noted. As for what needs to be noted include habitat, color, and substrate of the Bryophyte. The results of this study obtained 19 samples from Air Terjun Sigerincing and after identification, there were 12 Bryophytes species in the Air Terjun Sigerincing area of the 3 different classes and most commonly found were Bryopsida classes of 9 species, Anthocerotopsida 2 species and Tetraphidopsida 1 species.